MELAKA LEADS IN ENERGY EFFICIENCY BEST PRACTICES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PUTRAJAYA, December 2015 The Historic City of Melaka has become the first state in the country to be selected for a programme on efficient energy use, hence becoming a role model to others in forming collaborations on energysaving efforts that will bring about a change in lifestyle.